PENERAPAN MODEL PEMBELAJARAN PROJECT, ACTIVITY, COOPERATIVE, EXERCISE (PACE) UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS DAN SELF-EFFICACY SISWA - Yossi Amanda; Iyon Maryono; Riva Lesta Ariany (Program Studi Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2025)
The study aims to analyze the improvement of students’ mathematical understanding and self-efficacy after learning with the PACE model. This study used a quasi-experimental method, with a population of all students from ten eighth-grade students of a junior high school in Bandung in the 2024/2025 academic year. The sample was determined purposively by two classes. Data collection was carried out using test instruments and questionnaires. Data analysis used a t-test on test results and descriptive analysis on self-efficacy scores. The results showed that the improvement of mathematical understanding of students who received learning with the PACE model was better than students who learned in conventional classes. This can be seen from the N-Gain value in the experimental class of 0.304 (medium category) and the N-Gain in the control class of 0.124 (low category). The level of self-efficacy of students in the experimental class increased by 66.86 after learning with the PACE model. Thus, the PACE model is said to be effective in improving students’ mathematical understanding and self-efficacy. Further research is expected to identify the relationship between variables.